2017
DOI: 10.1101/203224
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genome-wide and high-density CRISPR-Cas9 screens identify point mutations inPARP1causing PARP inhibitor resistance

Abstract: PARP inhibitors (PARPi) target homologous recombination defective tumour cells via synthetic lethality. Genome-wide and high-density CRISPR-Cas9 "tag, mutate and enrich" mutagenesis screens identified single amino acid mutations in PARP1 that cause profound PARPi-resistance. These included PARP1 mutations outside of the DNA interacting regions of the protein, such as mutations in solvent exposed regions of the catalytic domain and clusters of mutations around points of contact between ZnF, WGR and HD domains. … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
38
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 51 publications
(88 reference statements)
5
38
0
Order By: Relevance
“…The RAD51 assay has some limitations: firstly, when PARPi sensitivity occurs via mechanisms that do not directly impact on the ability of cells to perform HRR, e.g., alterations in ATM (Chen et al , ; Davies et al , ; preprint: Balmus et al , ) or in the RNASEH2 complex (Zimmermann et al , ); secondly, when PARPi sensitivity occurs via mechanisms that preserve RAD51 foci formation, e.g., alterations in the MRN complex, RAD51AP1, polymerase eta, or ERCC1 (Kawamoto et al , ; Wiese et al , ; Oplustilova et al , ; Postel‐Vinay et al , ); thirdly, when HRR‐deficient tumors have acquired PARPi resistance via RAD51‐independent mechanisms such as loss of PARG, mutations in PARP1, or those that involve replication fork stabilization (Guillemette et al , ; Chaudhuri et al , ; Kais et al , ; Yazinski et al , ; Gogola et al , ; Michelena et al , ; Pettitt et al , ); fourthly, when a tumor has low proliferation index or low endogenous DNA damage, in which cases the assay would not be feasible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The RAD51 assay has some limitations: firstly, when PARPi sensitivity occurs via mechanisms that do not directly impact on the ability of cells to perform HRR, e.g., alterations in ATM (Chen et al , ; Davies et al , ; preprint: Balmus et al , ) or in the RNASEH2 complex (Zimmermann et al , ); secondly, when PARPi sensitivity occurs via mechanisms that preserve RAD51 foci formation, e.g., alterations in the MRN complex, RAD51AP1, polymerase eta, or ERCC1 (Kawamoto et al , ; Wiese et al , ; Oplustilova et al , ; Postel‐Vinay et al , ); thirdly, when HRR‐deficient tumors have acquired PARPi resistance via RAD51‐independent mechanisms such as loss of PARG, mutations in PARP1, or those that involve replication fork stabilization (Guillemette et al , ; Chaudhuri et al , ; Kais et al , ; Yazinski et al , ; Gogola et al , ; Michelena et al , ; Pettitt et al , ); fourthly, when a tumor has low proliferation index or low endogenous DNA damage, in which cases the assay would not be feasible.…”
Section: Discussionmentioning
confidence: 99%
“…or in the RNASEH2 complex(Zimmermann et al, 2018); secondly, when PARPi sensitivity occurs via mechanisms that preserve RAD51 foci formation, e.g., alterations in the MRN complex, RAD51AP1, polymerase eta, or ERCC1(Kawamoto et al, 2005;Wiese et al, 2007;Oplustilova et al, 2012;Postel-Vinay et al, 2013); thirdly, when HRR-deficient tumors have acquired PARPi resistance via RAD51independent mechanisms such as loss of PARG, mutations in PARP1, or those that involve replication fork stabilization(Guillemette et al, 2015;Chaudhuri et al, 2016;Kais et al, 2016; Yazinski et al, 2017;Gogola et al, 2018;Michelena et al, 2018;Pettitt et al, 2018);…”
mentioning
confidence: 99%
“…Then, we silenced the PARP1 gene in RD-ES and SK-ES-1 cells and proved the dependency of PARPis' cytotoxicity on PARP1 in both cell lines. 42 For example, PARP1 mutations are present in talazoparibresistant BRCA1-deficient SUM149 and COV362 cells, and a R591C mutation was associated with olaparib resistance in an ovarian cancer patient. Complementation of the KO cells with WT-or E988K-PARP1 showed that the cytotoxicity and PARP1-DNA trapping induced by talazoparib were dependent on the polymerase activity of PARP1, because purified E988K-PARP1 and WT-PARP1 proteins had similar capabilities to bind NAD + , PARPi and DNA.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the mutations reducing PARP1 polymerase activity have been found to cause cellular and clinical resistance to PARPis. 42 For example, PARP1 mutations are present in talazoparibresistant BRCA1-deficient SUM149 and COV362 cells, and a R591C mutation was associated with olaparib resistance in an ovarian cancer patient.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, cells with PARP1 mutations were 100‐fold more resistant to PARP inhibitors than were cells with wild‐type PARP1 . Mutations both within and outside the PARP1 DNA‐binding domains alter PARP1 trapping and induce PARP inhibitor resistance . Cancer cells may up‐regulate the HR repair pathway to compensate for the loss of BER as a result of PARP1 inhibition, and the HR and BER pathways interact to regulate cancer cell viability via decreased PARP1 and increased RAD51 expression levels.…”
Section: Mechanisms Underlying Parp Inhibitor Resistancementioning
confidence: 99%